Teak Soils - Seth, S. K.; Yadav, J. S. P. (Indian Forester, 1959)
The data on geology and soil of teak forests representing natural as well as artificial conditions with special reference to India, Pakistan, Burma and Indonesia have been described in detail. The optimum conditions of soil, elevation, topography, moisture, etc., required for the normal teak growth have been indicated. The feasibility of relationship between the different geological formations and the composition and distribution of teak forests has been elucidated. The requirement of teak for soil pH and lime has been critically examined. The nature and extent of soil deterioration consequent on clear-felling a natural forest and planting the same with teak have been discussed.